Single-cell sequencing uncovers sensory neuron–mediated CGRP signaling as a driver of sarcoma progression - Sowmya Ramesh; Qizhi Qin; Zhao Li; Masnsen Cherief; Lingke Zhong; Mary Archer; Xin Xing; Neelima Thottappillil; Devadutta Balaji; Sam Bae; Mario Gomez-Salazar; Mingxin Xu; et al. (Proceedings of the National Academy of Sciences, 2025)
Bone pain is a presenting feature of bone cancers such as osteosarcoma (OS), relayed by skeletal-innervating peripheral afferent neurons. Potential functions of tumor-associated sensory neurons in bone cancers beyond pain sensation are unknown. To uncover neural regulatory functions, a chemical-genetic approach in mice with a knock-in allele for TrkA was used to functionally perturb sensory nerve innervation during OS growth and disease progression. TrkA inhibition in transgenic mice led to significant reductions in sarcoma-associated sensory innervation and vascularization, skewed tumor associated macrophage polarization, reduced tumor growth and metastasis, and prolonged overall survival. Single-cell transcriptomics revealed that sarcoma denervation was associated with phenotypic alterations in both OS tumor cells and cells within the tumor microenvironment, and with reduced calcitonin gene-related peptide (CGRP) and vascular endothelial growth factor (VEGF) signaling. Multimodal and multiomics analyses of human OS bone samples further implicated peripheral innervation and neurotrophin signaling in OS tumor biology. Next and in two parallel approaches to inhibit nerve ingrowth, we repurposed FDA-approved bupivacaine liposomes and separately blocked CGRP signaling using FDA-approved Rimegepant. Both strategies led to significant reductions in sarcoma growth, vascularity, and sarcoma-induced hyperalgesia. In sum, TrkA-expressing peripheral neurons positively regulate key aspects of OS progression and sensory neural inhibition disrupts CGRP signaling within the sarcoma microenvironment leading to significantly reduced tumor growth and improved survival. These data suggest that interventions to prevent pathological innervation of OS represent an adjunctive therapy to improve clinical outcomes and survival.